Breast explant surgery: An integrative literature review (Research, Society and Development, 2023)
Breast explantation is the removal of the silicone prosthesis, mainly for health reasons, resulting from the body's immunological response mediated by cytokines and interleukins. After analyzing the studies, despite showing a need for more research to truly prove the association between silicone implants and the development of clinical conditions, it was found that the crucial reason for seeking the removal of silicone implants is the possible complications. related to prostheses, such as adjuvant-induced inflammatory syndrome (ASIA), silicone disease (BII), lymphomas and seromas. Therefore, with the upward movement of body self-acceptance and the alleviation of symptoms, such as fatigue, arthralgia, myalgia, neurasthenia, chest pain and photosensitivity in some patients undergoing breast explants, the demand for this procedure is increasingly frequent.